2021
DOI: 10.3389/fpsyt.2021.798909
|View full text |Cite
|
Sign up to set email alerts
|

Stigma Levels Toward Psychiatric Patients Among Medical Students—A Worldwide Online Survey Across 65 Countries

Abstract: Background: According to epidemiological data, over 450 million people worldwide suffer from mental disorders, presenting one of the major challenges of modern medicine. In their everyday lives, patients, in addition to fighting the disease itself, often struggle with stigmatization. This phenomenon negatively affects both the diagnostic and therapeutic processes, as well as the patients' everyday functioning. This study aimed to assess stigma attitudes toward psychiatry and psychiatric patients among undergra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 49 publications
1
16
1
Order By: Relevance
“…The decrease in the follow-up scores can be considered an indicator of the decrease in the students stigmatizing ideas. These results are consistent with the literature (Babicki, Małecka, Kowalski, Bogudzińska, & Piotrowski, 2021;Desai et al, 2019;Masedo et al, 2021). Similarly, Simon and Verdoux (2018) report significant changes after an educational program with Psychiatry and Neurology students.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The decrease in the follow-up scores can be considered an indicator of the decrease in the students stigmatizing ideas. These results are consistent with the literature (Babicki, Małecka, Kowalski, Bogudzińska, & Piotrowski, 2021;Desai et al, 2019;Masedo et al, 2021). Similarly, Simon and Verdoux (2018) report significant changes after an educational program with Psychiatry and Neurology students.…”
Section: Discussionsupporting
confidence: 90%
“…Also, collabora- tion with different disciplines with intervention design and application is of utmost importance, such as psychology, sociology, social work, etcetera. The most successful intervention should result from interdisciplinary work (Babicki et al, 2021;Corrigan et al, 2018;Potts et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with previous evidence suggesting that specific training in mental illness-related stigma may improve knowledge about mental health, but not the attitudinal and behavioral aspects of stigma toward mental health ( 41 ). It is of great concern that stigmatization and negative perceptions occur among medical students despite the provision of medical education and information about mental illnesses and their treatments ( 9 , 12 , 13 ). Therefore, anti-stigma interventions should adopt a multi-dimensional approach, go beyond theoretical knowledge, and separately target and assess improvements in attitudes and behaviors ( 7 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most observational studies on attitudes and stigma toward mental illness have focused on the general population and healthcare workers, while only a few ( 10 13 ) have been conducted with medical students. Nonetheless, there is no evidence supporting the absence of stigma in this group.…”
Section: Introductionmentioning
confidence: 99%
“…However, stigmatization of people with mental disorders was common in early career professionals [ 12 ]. A worldwide online survey across 65 countries showed that stigma toward both psychiatry and psychiatric patients was common among undergraduate medical students [ 13 ]. Medical students and nursing students believed that people with mental disorders symbolized aggression as well as unpredictability, and would never be able to recover sufficiently [ 14 ].…”
Section: Introductionmentioning
confidence: 99%